Union with Christ : in Scripture, history, and theology - Letham, Robert (Phillipsburg, P&R Publishing, 2011)
Union with Christ is the central truth of the whole biblical teaching about salvation. The entirety of our relationship with God can be summed up in this doctrine. Yet when people ask what this union actually is, we flounder. The incarnation shows that God has made us to be united with him, and God has given us his Word to enable us to understand the nature of this union. Set out with Robert Letham to explore this doctrine from Scripture -- using help from the church fathers to modern theologians. - Publisher.
Creation -- Incarnation -- Pentecost -- Union with Christ and representation -- Union with Christ and transformation -- Union with Christ in death and resurrection.
Includes bibliographical references (p. 143-152) and indexes.
Keywords: Jesus Christ -- Person and offices; Mystical union; Reformed Church -- Doctrines